2005
DOI: 10.3171/spi.2005.2.1.0017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spinal and general anesthesia in lumbar laminectomy surgery: a case-controlled analysis of 400 patients

Abstract: Object. Despite a history of safety and efficacy, spinal anesthesia is rarely used in lumbar surgery. Application of regional anesthetics is widely preferred for lower-extremity surgery, but general anesthesia is used almost exclusively in spine surgery, despite evidence that spinal anesthesia is as safe and may offer some advantages. Methods. In this case-controlled study the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
146
3
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(159 citation statements)
references
References 15 publications
6
146
3
4
Order By: Relevance
“…45,64 In contrast, studies in which either intrathecal fentanyl or sufentanil was utilized reported lower incidence rates ranging from 0 to 25%. 12,16,18,46,48,57,61 Kamphuis et al…”
Section: Resultsmentioning
confidence: 99%
“…45,64 In contrast, studies in which either intrathecal fentanyl or sufentanil was utilized reported lower incidence rates ranging from 0 to 25%. 12,16,18,46,48,57,61 Kamphuis et al…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings have been reported by others while comparing GA with RA for BMH, as well as for another surgical procedures. 6,7,11,13,14 In an earlier retrospective study of 162 BM donations (63 allogeneic and 99 autologous), Lavi et al 4 found that patients who underwent GA required more RBC units than those undergoing RA. Our results do not confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
“…However, as known from other patient groups, one might expect some important differences in outcome depending on anaesthesia method. 8,[12][13][14] Available data suggest reduced mortality and morbidity among patients undergoing surgical procedures under RA. On the other hand, as a result of progress in SCT techniques and supportive care in recent years, there is a tendency to raise the age limit for BM donors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations